2015
DOI: 10.1093/nar/gkv1074
|View full text |Cite|
|
Sign up to set email alerts
|

CstF-64 and 3′-UTRcis-element determine Star-PAP specificity for target mRNA selection by excluding PAPα

Abstract: Almost all eukaryotic mRNAs have a poly (A) tail at the 3′-end. Canonical PAPs (PAPα/γ) polyadenylate nuclear pre-mRNAs. The recent identification of the non-canonical Star-PAP revealed specificity of nuclear PAPs for pre-mRNAs, yet the mechanism how Star-PAP selects mRNA targets is still elusive. Moreover, how Star-PAP target mRNAs having canonical AAUAAA signal are not regulated by PAPα is unclear. We investigate specificity mechanisms of Star-PAP that selects pre-mRNA targets for polyadenylation. Star-PAP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…The mRNAs of these genes are polyadenylated by Star-PAP, a non-canonical poly(A) polymerase. 21 These observations suggest that for some pA sites, the DSE may represent the critical core element that drives cleavage efficiency and directs how the 3′end machinery is assembled at the pA site.…”
Section: Core Cleavage and Polyadenylation Sequence Elementsmentioning
confidence: 94%
See 2 more Smart Citations
“…The mRNAs of these genes are polyadenylated by Star-PAP, a non-canonical poly(A) polymerase. 21 These observations suggest that for some pA sites, the DSE may represent the critical core element that drives cleavage efficiency and directs how the 3′end machinery is assembled at the pA site.…”
Section: Core Cleavage and Polyadenylation Sequence Elementsmentioning
confidence: 94%
“…This Star-PAP mediated selection of pA sites may play a role in the regulation of APA. 21 PABPC1 No obvious cis -element enriched around pA sites regulated by PABPC1, but, like PABPN1, promotes distal pA site usage. Shuttles between the cytoplasm and nucleus and may regulate cytoplasmic polyadenylation.…”
Section: Factors That Regulate Active Apa By Influencing Pa Sites Chomentioning
confidence: 99%
See 1 more Smart Citation
“…Star-PAP targets distinct mRNAs involved in the oxidative-stress response, apoptosis, and cancer, and this targeting is independent of PAPα for the reported mRNAs ( 17 20 ). We have demonstrated that Star-PAP specificity for its target mRNAs is driven by a recognition sequence at the 3′-UTR, followed by exclusion of the canonical PAP via a suboptimal downstream sequence (DSE) located on its target mRNA UTR ( 21 ). While Star-PAP functions without certain cleavage factors, such as CstF-64, it requires additional associated proteins ( 17 , 19 , 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that Star-PAP specificity for its target mRNAs is driven by a recognition sequence at the 3′-UTR, followed by exclusion of the canonical PAP via a suboptimal downstream sequence (DSE) located on its target mRNA UTR ( 21 ). While Star-PAP functions without certain cleavage factors, such as CstF-64, it requires additional associated proteins ( 17 , 19 , 21 , 22 ). Moreover, as opposed to the canonical mechanism, Star-PAP directly binds the target mRNA and plays a structural role to help assemble the cleavage and polyadenylation complex ( 23 ).…”
Section: Introductionmentioning
confidence: 99%